A higher-order strain gradient plasticity theory with a corner-like effect. (April 2015) - Kuroda, Mitsutoshi
Abstract: A corner-like plasticity model originally proposed as a size-independent theory is extended to include a size effect resulting from plastic strain gradients. A method of solving boundary value problems at finite strains is also presented. The efficiency of the new theory is demonstrated through two typical numerical examples: a constrained simple shear problem in which an infinitely long strip bounded by two hard materials is subjected to large shear under plane strain conditions, and a problem of shear band formation in plane strain tension.